Addressing the Palestinian Cause by Talk shows of Russia Today and Alhurra June 2014- May 2015 - Ali Suleiman, Rasha Mohammed; Abu Arja, Tayseer (ALBAHITH ALALAMI, 2018)
The purpose of this analytical study is to showcase how Russia Today and U.S Alhurra channels addressed the Palestinian Cause between the periods of mid-2014 and mid-2015. In addition, the study aims to highlight the “significance levels” of the Palestinian Cause in both channels.The study is based on a rigorous survey methodology adopted by the researcher and based on the content analysis of Russia Today’s “Panorama” talk show and Alhurra’s “Free Hour show”.First level examination included the content analysis of 398 talk show episodes broadcasted by both channels during the period through which the study was conducted.Second level examination featured a detailed analysis of 38 episodes covering Palestinian Affairs aired by both channels during the same period.The study found several results, most notably:• Among all issues addressed by both programs during the period of the study, the Palestinian Cause ranked 4th in terms of coverage priority in both programs, with very similar levels of “interest” across both channels. Iraq spearheaded the coverage and attention of Alhurra’s “Free Hour”, while the major focus of RT’s “Panorama” primarily revolved around terrorism.• For both shows, the War on Gaza took the front seat among the overall Palestinian issues discussed during the period of the study.• Political topics dominated the majority of topics addressed by both programs during the study period including the Palestinian cause, while topics pertaining to the cultural, economic and humanitarian nature of the Palestinian Cause were generally neglected. Alhurra’s “Free Hour show” was found to ignore these issues more often.